Integrative assessment and management implications on loss of ecosystem services value of desert-oasis ecotone due to artificial oasis expansion - Xinxin Li; Donglei Mao; Jie Xue; Shunke Wang; Jingjing Chang; Xin Liu (Global Ecology and Conservation)
The ecosystem services value (ESV) is essential for preventing environmental degradation and biodiversity loss. The expansion of artificial oases has led to a decrease in ESV in the desert-oasis ecotone of arid regions. The southern Tarim Basin represents a typical arid ''mountain-oasis-desert system.'' This study employs the CA-Markov model, the ESV evaluation model, and the geographical detector model to simulate future scenarios and assess the attribution of Land-Use and Land-Cover Change (LUCC) and the loss of ESV in the desert-oasis ecotone of the southern Tarim Basin, China, from 2000 to 2030. From 2000–2020, the area of artificial oases expanded by 44.1 %, resulting in a loss of 5.653 billion yuan in ESV within the desert-oasis ecotone. This highlights the threat to the stability of the oasis ecosystem caused by the expansion of artificial oases in the region. In the three scenario simulations for 2030, the ecological protection scenario predicts the smallest expansion of artificial oasis area (1.27 %) compared to 2020. Additionally, it has the lowest loss of ESV in the desert-oasis ecotone (860 million yuan). This suggests that future implementation of ecological protection policies could effectively safeguard the ESV in the desert-oasis ecotone. DEM, GDP and NDVI are the main factors influencing ESV loss in the desert-oasis ecotone. The ESV assessment framework and future scenario simulation results presented in this study can offer scientific evidence for policymakers, aiding in the formulation and implementation of more effective ecological protection policies. This approach is also beneficial for ecological conservation and restoration in the context of accelerated urbanization.